IMPLEMENTASI EKSPERIMEN BLACK CARAMEL SEBAGAI MEDIA EDUTAINMENT KIMIA - Nora Listantia; Lusia Novita Ramadhani (PELITA NUSA TENGGARA, 2026)
This study aimed to implement an edutainment-based learning medium through a Black Caramel Project in chemistry learning to foster undergraduate students' critical thinking skills. Chemistry education should not only emphasize conceptual understanding but also develop students' ability to apply scientific knowledge in solving real-world problems. However, many students remain passive during the learning process, resulting in underdeveloped critical thinking skills. The Black Caramel Project was implemented as an edutainment medium that integrates educational and entertaining elements through a hands-on sugar caramelization experiment. The study employed a literature review combined with project implementation in a chemistry laboratory using lecture and demonstration approaches. The implementation demonstrated that the Black Caramel Project enhanced students' understanding of fundamental chemical concepts, including carbohydrate structure, caramelization reactions, physical and chemical changes, and their applications in the food industry. Furthermore, students became more actively engaged in analyzing experimental processes, evaluating results, and solving problems encountered during the activity, thereby fostering their critical thinking skills. Overall, the implementation of the Black Caramel Project as a chemistry edutainment medium represents an innovative and meaningful practice-based learning approach that creates an enjoyable learning environment while supporting the development of students' critical thinking skills.